Natural New Sesquiterpenes: Structural Diversity and Bioactivity - Li, Dan; Wang, Kui-Wu (Current Organic Chemistry, 2016)
Sesquiterpenoids, consist of 15 carbons backbone, may play a highly significant role in natural products. There are various types of the sesquiterpenoids due to different spatial configurations via modification and rearrangement. Sesquiterpenoids exhibit various biological activities: anti-tumor, anti-viral, anti-microbial, anti-inflammatory and so on. The study on sesquiterpenes may receive more and more attentions, and will increase the chance to discover bio-active drug leads with medicinal potential. The present paper reviews the latest progress in the structural diversity and the biological activity of the new sesquiterpenes isolated from natural resource in recent years. Overall, 337 compounds, and 201 references are presented.
Keywords: Sesquiterpenoids